Financial Sector Assessment Program : Saudi Arabia - CPSS Core Principles for Systematically Important Payment Systems - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
The present document is the assessment of the systemically important payment systems in the Kingdom of Saudi Arabia (KSA) based on the CPSS Core Principles for Systemically Important Payment Systems (CPSIPS). The document also contains an analysis of some developmental issues related to the reform of the payments system as a whole. The assessment was conducted in the context of the field mission of the Financial Sector Assessment Program (FSAP) Update to the KSA (April 2011). The assessor of the CPSIPS was Massimo Cirasino. The national payments system (NPS) in Saudi Arabia efficiently serves the needs of a broad set of users. In particular, SAMA has implemented a comprehensive and robust infrastructure to support the provision of payment services and products by commercial banks. The infrastructure is primarily concentrated on payments in riyals and comprises the following systems: (i) the Saudi Arabian Riyal Interbank Express (SARIE) real time gross settlement (RTGS) system, which processes a wide range of large-value and small-value payments and provides settlement facilities for a number of clearing systems, as well as for transactions executed at the Tadawul stock exchange; (ii) the check clearing houses operated at SAMA branches; (iii) automated teller machine (ATM) and point-of-sale services provided through Saudi payments network; (iv) electronic bill presentment and payment processed by the national electronic bill presentment and payment service; (v) the Public Key Infrastructure (PKI) which provides advanced security facilities; and (vi) the SAMA Joint Network (SJN) providing a highly secured communications network. The NPS in Saudi Arabia is characterized by a high level of standardization.